Peer Support and Mental Health: A Study Among Adolescents - Evi Ni'matuzzakiyah; Nazhif Masykur (Lembaga Pengembangan Kinerja Dosen, 2026)
Peer support is an important social factor that contributes to adolescents' psychological development. Insufficient peer support may increase the risk of mental health problems among adolescents. This study aimed to examine the correlation between peer support and adolescent mental health problems among students of SMP Negeri 1 Pandak, Bantul Regency, Special Region of Yogyakarta, Indonesia. This study employed a quantitative approach with a cross-sectional design. A total of 67 students were recruited using an accidental sampling technique. Data were collected using a peer support questionnaire and an adolescent mental health problems questionnaire. Data analysis was performed using Kendall's Tau correlation test. The results showed that the majority of respondents reported low peer support (56.7%) and very severe mental health problems (86.6%). Kendall's Tau analysis revealed a significant correlation between peer support and adolescent mental health problems (τ = -0.317; p = 0.004). The negative correlation coefficient indicates that higher levels of peer support were associated with lower levels of mental health problems among adolescents. These findings suggest that peer support plays an important protective role in maintaining adolescent mental health. Strengthening positive peer relationships may contribute to the prevention and reduction of mental health problems among adolescents.